The interval shuttle run test for intermittent sport players: evaluation of reliability - Lemmink, K. A. P. M.; Visscher, C.; Lambert, M. I.; Lamberts, R. P. (The Journal of Strength and Conditioning Research, 2004)
The reliability of the interval shuttle run test (ISRT) as a submaximal and maximal field test to measure intermittent endurance capacity was examined. During the ISRT, participants alternately run for 30 seconds and walk for 15 seconds. The running speed is increased from 10 km·h-1 every 90 seconds until exhaustion. Within a 2-week period, 17 intermittent sport players (i.e., 10 men and 7 women) performed the ISRT twice in a sports hall under well-standardized conditions. Heart rates per speed and total number of runs were assessed as submaximal and maximal performance measures. Results: With the exception of the heart rates at 10.0 km·h-1 for men and 10.0, 12.0, and 13.5 km·h-1 for women, zero lay within the 95% confidence interval of the mean differences, indicating that no bias existed between the outcome measures at the 2 test sessions (absolute reliability). The results illustrate that it is important to control for heart rate before the start of the ISRT. Relative reliability was high (intraclass correlation coefficient 0.86). We conclude that the reliability of the ISRT as a submaximal and maximal field test for intermittent sport players is supported by the results.